Willingness of emergency and medicine department doctors to work during surge of COVID-19 patients, Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Introduction: With the current COVID-19 pandemic, Patan Hospital, Patan Academy of Health Sciences (PAHS), is responding with its incident action plan which also has provision of the response in case of surge. This study aim to find out the willingness of doctors to work during the surge of COVID-19 and may help in further planning.Method: A cross-sectional descriptive study was conducted at Patan Hospital, PAHS, Nepal in April 2020. Questionnaires were circulated to the doctors via Google form to the doctors working in the emergency and medicine department. Ethical approval was obtained. Data were analyzed descriptively.Result: Out of total 73 participants, 59 (80.8%) knew about the surge plan of COVID-19 and 54 (73.9%) were willing to work during the surge. Their major motivation was the professional obligation 56 (76.7%), whereas 61(83.6%) fear about their family getting infected. More than 50% of the participants were ready to stay in-house and work in a sub-optimal environment with a feeling of making a significant contribution to the community.Conclusion: When the number of cases of COVID-19 peaks and the surge plan gets activated, the majority of doctors surveyed were found willing to work even in sub optimal environments.